The Effect of Relativistic Quantum Corrections on the Thermal Properties of Three-Dimensional Spherical Semiconductor Quantum Dot Under a Magnetic Field (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2018)
The ground state and excited states energies of 2-electron quantum dot with spherical harmonic oscillator type potential has been determined. The energy spectrum and wave functions for the quantum dot of asymmetric confinement are obtained by analytically solving the eigenvalue equation in the magnetic field. The effect of various relativistic corrections to kinetic energy, Darwin term and spin-orbit for the zero-dimensional structure to the energy eigenvalues and wave functions is also investigated. The thermal properties like internal energy, entropy and free energy are discussed graphically with radius of quantum dot and pressure and are found to have interesting dependence on the radius and pressure parameter with relativistic corrections for our model.
Keywords: Quantum dot; Magnetic field; Relativistic corrections; Pressure; Thermodynamic properties